Biscarboxy-Functionalized Imidazole and Palladium as Highly Active Catalytic System in Protic Solvents: Methanol and Water - Martínez, Regina; Pastor, Isidro M.; Yus, Miguel (Synthesis, 2014)
The coupling reaction between aryl bromides and boron reagents is efficiently catalyzed by an in situ generated palladium complex obtained from palladium(II) acetate (0.1 mol%) and 1,3-bis(carboxymethyl)imidazole (0.2 mol%). The catalytic system is very active in protic solvents, especially in methanol. Biaryl derivatives have been prepared in good isolated yields (up to >99%), and additionally styrene and stilbene derivatives have also been prepared by means of this protocol.
Keywords: palladium; organometallic reagents; heterocycles; solvent effects; cross-coupling